PROTEIN CATABOLIC RATE SHOULD BE NORMALIZED BY IDEAL BODY WEIGHT NOT BY POST-DIALYSIS BODY WEIGHT. - Ikuto Masakane; Mika Nakajima; Miho Suzuki; Yumiko Seino; Kiyotaka Yabuki (The Korean Society of Nephrology, 2012)
Protein catabolic rate (PCR) is calculated by urea kinetic model thorough the dialysis session and it is recognized as expressing the protein intake in the steady state of dialysis patients. PCR is generally normalized by post-dialysis body weight (BW), expressed as nPCR, however, most dietary guidelines for protein intake are documented as PCR normalized by ideal BW (iPCR). We evaluated which is better nPCR or iPCR to estimate the impact on the patient survival and to use it for dietary education for dialysis patients. 119 chronic dialysis patients whose dialysis vintages were longer than 3 years were selected into this study. The mean age of them was 62.4years old and the mean dialysis vintage was 115.4 months. The patients were divided into 4 groups by each PCR value as less than 0.7, 0.7- 0.9, 0.9-1.1, greater than 1.1 g/Kg/day. Kaplan-Meier analysis was conducted to evaluate the 5-year patient survival in each PCR method. The difference in the patient survival between 4 groups in each PCR method was evaluated by Log-rank test. Among 119 patients 30 patients died and 9 patients were censored out, and the overall 5-year survival rate was 74.4%. There were no significant differences between 4 groups in nPCR. However, a significant risk in the group less than 0.7 g/Kg/day and a significant benefit in the group greater than 1.1 g/Kg/day were observed in iPCR. Both nPCR and iPCR were not independent significant risk factor on the patient survival. Only age and the serum level of CRP were significant risk factor. We concluded the PCR should be normalized by ideal BW not by post-dialysis BW.